Productions and uses of statistics in Nigeria - Muhammed, B. A.; Nigeria; Nigerian Institute of Social and Economic Research (Ibadan : Nigerian Institute of Social and Economic Research ; Lagos : Federal Office of Statistics, 1983)
This book discusses plans and steps involved in production of statistics with special reference to Nigerian experience.
Based on the National Workshop on Productions and Uses of Statistics sponsored by the Federal Office of Statistics (FOS) in conjunction with the Nigerian Institute of Social and Economic Research (NISER) between Feb. 22, 1982 and Feb. 24, 1982.
MF22/01/2019
Loan
Keywords: Social surveys; Economic surveys; Nigeria